Gastric Foreign Bodies in Prison Inmates - Kumar, Manish; Sachdeva, Sanjeev; Kumar, Ajay; Sonika, Ujjwal; Gupta, Manish; Srivastava, Siddharth; Dahale, Amol; Dalal, Ashok (Journal of Digestive Endoscopy, 2021)
Objective Gastric foreign bodies are a common problem brought to an endoscopist. Prisoners are more prone to ingesting unusual foreign bodies for a secondary gain. The objective of this study was to study the profile of foreign body ingestion among the prisoners brought to a tertiary care center.Methods This is a retrospective case series. All the prisoners brought for endoscopic removal of foreign bodies between January 2018 to December 2019 were included in the analysis. Patients’ baseline characteristics, type of foreign body, management, and outcome were notedResults A total of eight inmates presented with ingestion of foreign body to our department. Most common foreign bodies ingested were drug packets and mobile phones. All ingestions were for secondary gain. Endoscopic removal was successful in all cases.Conclusion Endoscopic removal can be tried with all necessary precautions by an expert endoscopist.
Keywords: mobile phone ingestion; prisoners; endoscopic removal of mobile phone; gastric foreign bodies; unusual foreign bodies ingestion